If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + 3x) * 4 + -2x = 0 Reorder the terms for easier multiplication: 4(5 + 3x) + -2x = 0 (5 * 4 + 3x * 4) + -2x = 0 (20 + 12x) + -2x = 0 Combine like terms: 12x + -2x = 10x 20 + 10x = 0 Solving 20 + 10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 10x = 0 + -20 Combine like terms: 20 + -20 = 0 0 + 10x = 0 + -20 10x = 0 + -20 Combine like terms: 0 + -20 = -20 10x = -20 Divide each side by '10'. x = -2 Simplifying x = -2
| 3p-7q+14p-8q= | | 12a+12y=48 | | 10k-3k+5h+2h= | | 8b+4-4=-15+15b | | 13x+7(-3x-1)=-13 | | 86=b-10 | | 0=2+15x-4.9x^2 | | 6z+11=9 | | 5n+5n=5n+10 | | 12y+24c=36 | | 3(x-3)=x-3(x+2) | | 12a+24y=36 | | 3x+9y=36 | | x=4+-4.5y | | 5-8v+4v=4v+5 | | 2x+9y=8 | | 0=-16t^2+80t+5 | | -4x-11[x+7]=-2[7x+4] | | 6a+12y=18 | | y=5*-2+3 | | w+7=5w-5 | | -14-4n=-6n-5n | | 2n-9=95 | | y=5*-1+3 | | y=5*0+3 | | x^2-8*x+5=0 | | y=5*1+3 | | .2(5-.3x)=.16x+.208 | | 3y+6c=9 | | 2y+4c=6 | | y=5*2+3 | | (x^2-2)(x^2+2)(x^2+4)(x+2)(x-2)=0 |